Verification of Operating Principle of Nano Field-effect Transistor Biosensor with an Extended Gate Electrode - Kang, Hye-Lim; Yoon, Sumi; Hong, Dong-ki; Song, Sunga; Kim, Young Joo; Kim, Won-Hyo; Seong, Woo-Kyeong; Lee, Kook-Nyung (Biochip journal, 2020)
Many studies have been conducted on the use of nano field-effect transistor (nanoFET) sensors for the detection of biological species. However, the practical application of nanoFET-based biosensors is difficult because their operating principle has not been clarified. Most existing studies focused on ion concentration and pH level in a solution, the Debye length (the physical distance at which charged particles affect the electric field), and the surface potential of the gate electrode of the nanoFET device. In this study, we verified the operating principle of the nanoFET biosensor with an extended gate electrode and established an equivalent circuit. We experimented using a solution with different pH levels to demonstrate the operating principle of the sensor. Additionally, we analyzed the responses of the device based on the material of the extended gate electrode, the effects of the reference electrode, and the connection configuration of the electrodes. We derived an equivalent circuit to explain how the nanoFET sensor works. The analysis results show that the operating principle of measuring pH or biomolecules depends on the change of the polar capacitor in the liquid-electrode interface on the surface of the sensing electrode. The roles of the reference and extended gate electrodes were clearly explained in this paper. The results of this research will improve the understanding of the operating principle of nanoFET-based biosensors and accelerate the studies for practical biosensor applications of nanoFET devices.